Cost-Optimal Fuel Utilization, Genset Configuration and Battery Sizing: A Case-Study of a Norwegian Trawler - Tor Hennum; Øyvind Kåre Kjerstad; Ann R. Nerheim (Modeling, Identification and Control)
The energy transition of the Norwegian ocean-going fishing fleet is challenging since there are few widely available fuel alternatives. Many large fishing vessels stay at sea for long periods between each fuelling. To complete its tasks and have space for the caught fish, an energy system which efficiently utilizes its fuel is required. This work proposes a flexible optimization-based mixed-integer linear programming tool for sizing, scheduling and analysing maritime energy systems consisting of diesel gensets and batteries, which considers both part-load engine efficiency and battery degradation. The tool is applied on a 24-hour data selection from an existing trawler, and the results point to the main fuel savings being enabled by splitting the installed power capacity into smaller gensets that can run independently from each other, and from utilizing a battery system to both reduce the total installed genset capacity to increase their relative loading and by delaying the startup of new gensets. Smaller fuel savings can be achieved from peak shaving of already running gensets. The current application achieves a 7.3% fuel reduction in a cost-efficient manner over the period. It also suggests that a fuel-reducing system might not necessarily be cost-efficient, particularly for energy systems with small batteries.